Implementasi Pembelajaran Sikap Syukur Terhadap Perilaku Sosial - Nanik Indah lestari; Humai rosyaida; Risqia Ramadhani; Muhammad Romadlon Habibullah (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
This study aims to examine the concept of gratitude and the attitude of gratitude in grade IV students of MI Islamiyah AL Maliki Bojonegoro. In addition, this study also wants to understand the concept of character and the behavior of students' character in the class. In addition, this study aims to explore the role of gratitude in the formation of children's character. The method used in this study is a literature review research model. The results of the study indicate that character is an individual's awareness in acting in accordance with the norms and rules that apply in society. Meanwhile, gratitude is interpreted as a servant's recognition of God for the blessings given, accompanied by an attitude of submission to Him. From this study, it was revealed that most students of MI Islamiyah AL Maliki Bojonegoro have a high level of gratitude. This is evidenced by the fulfillment of all indicators of gratitude explained in the study of Sufism.